Bioethical Issues in Pyschiatric Treatment - Buffardi, Gianfranco (Studia Bioethica, 2012)
Every medical act has repercussions for the existence of the individual patient and of those closest to him or her. Such repercussions are all the more significant in psychiatry. Many of the choices facing the psychiatrist have major bioethical implications. The bioethical topics pertaining to mental health are at the heart of many declarations by national and international organizations; yet the topics they deal with by no means cover all the bioethical issues in psychiatry.This essay sets out to highlight some aspects of psychiatric treatment which have a strong bioethical impact and which do not receive much attention in the existing literature on bioethics. I have identified seven topics which, starting from epistemological premises, will focus on the sorts of dilemma psychiatrists inevitably encounter in their daily contact with patients.